If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -3 = 2 Reorder the terms: -3 + m = 2 Solving -3 + m = 2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + m = 2 + 3 Combine like terms: -3 + 3 = 0 0 + m = 2 + 3 m = 2 + 3 Combine like terms: 2 + 3 = 5 m = 5 Simplifying m = 5
| -56+38= | | -7*-7+6y=-42 | | 4a-8(-5-6a)=40-8a | | 11+3x-7=9 | | 106=-7(p-7)+1 | | -1=-10/9x+10 | | -1=-10/9+10 | | -16-5x=5-sx | | (4x-3)/5=(2x-7)/8 | | -1.1111=-10/9x+10 | | -1.1111=-10/9+10 | | 82=4x-2(1-4x) | | -10/9*-1.1111+10 | | 4/3*6.4615-8=y | | -1/2*-5 | | -x/2+5=-1 | | x/4-2=-7 | | 4(3g-5)=52 | | 2x-1=z+2 | | (4/3x)-8=(-8/7x)+8 | | 4/3-8=-8/-7+8 | | 4/3x-8=-8/7+8 | | 0=4/3x-8 | | -4+3x+2x=36 | | 0=-8/7x+8 | | 3/4m | | 3.8x=2.6x | | 0=-8/7+8 | | m+11=5m+9 | | 1/2p-7=9(-27) | | 1/2p-7(-27) | | -34-4x=13-10x |